PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM PENINGKATAN MUTU PENDIDIKAN DI MTsN 3 MEDAN - N. Cici Mahruliana (Universitas Negeri Medan, 2022)
The person responsible for coordinating efforts to improve education standards is the head of the madrasah. Because of the quality of education, graduates must be skilled, competent with appropriate capacities, honest, and moral. improve the quality of higher education in various ways, including improving educational facilities, producing and obtaining teaching materials, developing and perfecting curricula, evaluating systems, and training education staff. The descriptive analysis approach is combined with the qualitative approach in this study. Descriptive analysis is a research method that uses observable behavior and the written or spoken words of people who are used as research subjects to produce descriptive data that provide details about the phenomenon under study. Judging from the test findings, the form of authority used by the madrasah leadership at MTsN 3 Medan included that the madrasah leadership generally spoke with all heads of the teaching group, staff, and organizations before making any decisions.